IMPLEMENTASI ALGORITMA MAXIMAL SHIFT PADA APLIKASI MANFAAT TANAMAN BAGI KESEHATAN MANUSIA BERBASIS ANDROID - Abdul Rahman Pohan; Nelly Astuti Hasibuan; AM Hatuaon Sihite (STMIK Budi Darma, 2019)
Before the arrival of disease, it is good for humans to prevent it, many plants grow that are beneficial to health, but so are the many diverse types of plants and their respective benefits so that it is difficult to understand which are beneficial for health which are not beneficial for health. To facilitate the search for plant health benefits for human health, it was designed using the Maximal Shift algorithm, where this algorithm as a solution in searching for plant health benefits for human health with the limited screen size of smartphones owned, string matching is needed as a process in the search. Application search for the benefits of plants for human health based on Android was designed using Eclipse Juno. In the development of this application using the Java programming language.Keywords: Maximal Shift, String Matching, Application of Plant Benefits, Based on Android